2011
DOI: 10.1371/journal.pone.0017732
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation to the Cell-Penetrating Peptide TAT Potentiates the Photodynamic Effect of Carboxytetramethylrhodamine

Abstract: BackgroundCell-penetrating peptides (CPPs) can transport macromolecular cargos into live cells. However, the cellular delivery efficiency of these reagents is often suboptimal because CPP-cargo conjugates typically remain trapped inside endosomes. Interestingly, irradiation of fluorescently labeled CPPs with light increases the release of the peptide and its cargos into the cytosol. However, the mechanism of this phenomenon is not clear. Here we investigate the molecular basis of the photo-induced endosomolyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 44 publications
2
56
0
Order By: Relevance
“…This photon flux is approximately 3200 fold less than what has been reported for the irradiation of Fl-CPP trapped inside endosomes of live cells on an epifluorescence microscope (irradiance is high because of the focusing of light beam after 100× objective). For comparison purposes, 40 min irradiation with the described set-up is equivalent to 0.75 sec irradiation on a microscope, a time scale at which most endosomes are photolysed [7]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This photon flux is approximately 3200 fold less than what has been reported for the irradiation of Fl-CPP trapped inside endosomes of live cells on an epifluorescence microscope (irradiance is high because of the focusing of light beam after 100× objective). For comparison purposes, 40 min irradiation with the described set-up is equivalent to 0.75 sec irradiation on a microscope, a time scale at which most endosomes are photolysed [7]. …”
Section: Methodsmentioning
confidence: 99%
“…However, while photosensitizers generally generate singlet oxygen in relatively high yields, the fluorophores used to label CPPs typically have very poor singlet oxygen quantum yields [14, 15]. Studies with membrane models such as the plasma membrane of red blood cells (RBCs) indicate that generation of ROS is indeed involved in the photolytic activity of Fl-CPPs [7, 16]. Yet, these studies also suggest that the CPP moiety acts in synergy with the singlet oxygen-generating fluorophores to disrupt membranes efficiently [16].…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis and necrotic cell damage have been observed after laser excitation of R7-TPC and Tat-TMR [120, 127]. Cytoplasm membrane permeabilization and blebbing, and cell shrinkage were seen shortly after photo-illumination of TMR-TAT at 560 nm [127]. Another potential limitation of photochemically induced endosomolysis is the difficulty of in vivo light delivery.…”
Section: Endosome Disrupting Peptides Facilitating Sirna Endosomalmentioning
confidence: 99%
“…These studies did not identify the cause of cell death but on the other hand suggested that cells could survive partial lysosomal disruption [13]. We have recently reported that TAT labeled with tetramethylrhodamine, TMR-TAT, also kills cells readily upon light irradiation during PCI experiments [14]. TMR-TAT efficiently escapes from endosomes on a millisecond time scale when using an epifluorescence microscope as light source.…”
Section: Introductionmentioning
confidence: 99%
“…TMR-TAT efficiently escapes from endosomes on a millisecond time scale when using an epifluorescence microscope as light source. The fluorescent peptide is also photolytic toward biological membranes such as the plasma membrane of red blood cells [14]. These effects involve the targeting of TMR by TAT to cellular membranes and the formation of singlet oxygen within membranes.…”
Section: Introductionmentioning
confidence: 99%